2022
DOI: 10.1101/2022.04.01.486762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efflux-linked Accelerated Evolution of Antibiotic Resistance at a Population Edge

Abstract: How antibiotic-resistance mutations survive Darwinian forces in the absence of antibiotics is a long-standing question. We report an unexpected evolutionary phenomenon we call phenotype surfing wherein twin phenotypes - high mutation frequencies and high efflux - segregate at the advancing edge of moving E. coli swarms. These phenotypes are linked: high efflux causes downregulation of specific DNA repair pathways, elevating mutations. We uncovered a genetic network connecting efflux and DNA repair, which we co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Coding sequence mutations in efflux pumps have also been shown to increase antibiotic resistance in Pseudomonas aeruginosa (mexB, mexY), Klebsiella pneumoniae (kmrA), and Neisseria gonorrhoeae (mtrD), likely due to increased affinity for the antibiotic (53)(54)(55). Recent studies have suggested that increased expression of efflux pumps could also facilitate antibiotic resistance either by increasing the mutation rate (56,57), allowing expression of resistance determinants upon plasmid acquisition (58), or promoting selection of resistance mutations due to increased fitness upon antibiotic exposure of strains both carrying the resistance mutations and overexpressing efflux pumps (59). We also found that coding sequence mutations in the SdrM binding pocket increased DLX resistance and efflux, likely by altering the binding to DLX.…”
Section: Discussionmentioning
confidence: 99%
“…Coding sequence mutations in efflux pumps have also been shown to increase antibiotic resistance in Pseudomonas aeruginosa (mexB, mexY), Klebsiella pneumoniae (kmrA), and Neisseria gonorrhoeae (mtrD), likely due to increased affinity for the antibiotic (53)(54)(55). Recent studies have suggested that increased expression of efflux pumps could also facilitate antibiotic resistance either by increasing the mutation rate (56,57), allowing expression of resistance determinants upon plasmid acquisition (58), or promoting selection of resistance mutations due to increased fitness upon antibiotic exposure of strains both carrying the resistance mutations and overexpressing efflux pumps (59). We also found that coding sequence mutations in the SdrM binding pocket increased DLX resistance and efflux, likely by altering the binding to DLX.…”
Section: Discussionmentioning
confidence: 99%